Pengaruh Kepemimpinan Transformasional Kepala Sekolah Terhadap Pendidikan Multikultural - Suprapto, Raden Inton Tyas; Hariyati, Nunuk; Dewi, Utari; Khamidi, Amrozi; Amalia, Kaniati (LPPM Institut Pendidikan Nusantara Global, 2024)
Transformational leadership, as one of the most studied leadership theories, has great potential to support and strengthen the implementation of multicultural education. Transformational leadership is characterized by a leader's ability to inspire, motivate and empower followers to achieve positive change and improved performance. Multicultural education is urgently implemented in Indonesia by considering the diversity of cultures, ethnicities, races and religions that surround it. This article discusses a school leadership model that is expected to design, foster, implement and maintain a multicultural culture in schools which in turn can form students' personalities who are friendly and respectful of differences and diversity. The author uses the literature study method by reviewing 20 journals divided into 10 national and 10 international journals. Data collection is done by sorting reference sources and scientific literature related to theories of school leadership, transformational leadership models and multicultural education, then reviewing and analyzing and presenting them in a systematic arrangement. The conclusion in this article states that transformational leadership by school principals is very important to improve the quality of education and encourage continuous improvement in schools. Principals' exemplary behaviors, such as punctuality, cleanliness and proactive problem-solving, earn them respect and positively influence school culture. Multicultural leadership in schools is interpreted as the extent to which principals implement policies, regulations and initiatives that promote a multicultural culture that is not limited to written documents but also includes the enforcement of rules and regulations.